Successful test dry heat oven sterilizer on dental instruments sterilization in X Hospital - Amir, Arrahmi; Dewi, Warta; Wardani, Riana (Universitas Padjadjaran, 2013)
Introduction: Instruments used for dental examinations and treatment often come into contact with fluids and soft tissues found in the oral cavity. The contact while the dental treatment procedures can cause contaminated and potentially mediates the displacement of microorganisms from the mouth of the patient to the operator or to other patients. Sterilization is the most effective process for the decontamination of reusable equipment. The objective of this study was testing the success of dry heat oven sterilizer to dental instruments sterilization in X Hospital. Methods: This study used descriptive method. Data was obtained by bacteriological examination, with a random sampling technique and obtained a sample of five instruments. Results: The results show there is a growing colony of bacteria in each sample after examination materials were incubated at 37 ºC for 18-24 hours. Conclusion: The conclusions of this study are dry heat oven sterilizer not belong to the success criteria for dental instrument sterilization process in X Hospital.